Pengaruh Non Performing Loan (NPL) dan Return On Asset (ROA) Terhadap Penyaluran Kredit (Studi pada Bank Umum Konvensional yang Terdaftar pada Bursa Efek Indonesia Periode 2019-2021) - Aini Eka Putri, Nur; Asmeri, Rina; Yuli Ayu Putri, Sri (Ekasakti Pareso Jurnal Akuntansi, 2024)
This research aims to analyze and determine the influence of Non-Performing Loans (NPL) and Return on Assets (ROA) on Credit Distribution to Conventional Commercial Banks listed on the Indonesia Stock Exchange (BEI) for the 2019-2021 period. The data collection techniques used are websites and documentation. The data type is quantitative data with secondary data sources. The population used in this research is conventional commercial banks listed on the Indonesia Stock Exchange in 2019–2021, totaling 46 companies with purposive sampling, so the total sample is 13 companies x 3 years = 39 financial reports. The data analysis method in this research uses multiple linear regression analysis, coefficient of determination, and hypothesis testing T test and F test. The results of this research show that: 1. Non-Performing Loans (NPL) partially have a significant negative effect on bank credit distribution (PK). conventional general listed on the Indonesian Stock Exchange (BEI). 2. Return on Assets (ROA) does not partially have a significant effect on Credit Distribution (PK) of conventional commercial banks listed on the Indonesia Stock Exchange (BEI). 3. Non-Performing Loans (NPL) and Return On Assets (ROA) simultaneously have a significant positive effect on Credit Distribution (PK) of conventional commercial banks listed on the Indonesia Stock Exchange (BEI).